2007
DOI: 10.1021/jp0701688
|View full text |Cite
|
Sign up to set email alerts
|

Photochemical and Photophysical Properties of Three Carbon-Bridged Fullerene Dimers:  C121 (I, II, III)

Abstract: The photochemical and photophysical properties of the three C121 isomers (I, II, III) were investigated with MADLI-TOF-MS, UV-vis spectra, fluorescence spectra, absorption spectra of their DMA complexes, and theoretical calculations. The three isomers of C121 (I, II, III) have different stabilities under laser irradiation, but isomer I and isomer II show good stability against the heat-induced conversion between different isomers: No conversion between the isomers was found after heating the mixture of isomer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 46 publications
0
13
0
Order By: Relevance
“…3,4 Under the severe neutron irradiation condition, the yield of isomers should be totally dependent on their thermodynamic stabilities. 11 The theoretical calculations concluded that the most possible structures of C 131 and C 141 were both [6,6]- [6,6] connections, in which C 70 opened the [6,6] ring that located at the equator area to create new chemical bonds with the bridged carbon atom. 3,4 We speculated that the structure of C 131 and C 141 in this study should be a [6,6]- [6,6] connection, which was similar to that of C 121 (I).…”
Section: Resultsmentioning
confidence: 99%
“…3,4 Under the severe neutron irradiation condition, the yield of isomers should be totally dependent on their thermodynamic stabilities. 11 The theoretical calculations concluded that the most possible structures of C 131 and C 141 were both [6,6]- [6,6] connections, in which C 70 opened the [6,6] ring that located at the equator area to create new chemical bonds with the bridged carbon atom. 3,4 We speculated that the structure of C 131 and C 141 in this study should be a [6,6]- [6,6] connection, which was similar to that of C 121 (I).…”
Section: Resultsmentioning
confidence: 99%
“…40 Photochemical and photophysical properties of the three bridged isomers [6,6]–[6,6], [5,6]–[6,6], and [5,6]–[5,6] also have been reported. 41,42 …”
mentioning
confidence: 99%
“…According to the density functional theory results of C 60 dimer [57,58], the LUMOs are assumed slightly lowered in comparison with normal PC 61 BM. In fact, V oc of photovoltaic devices incorporating PC 61 BM nanowires is decreased, and further decreased with increasing the number density and length of PC 61 BM nanowires.…”
Section: Photovoltaic Application Of Nanowiresmentioning
confidence: 99%